My experiences with the poorest of the poor - Naidu, T. Baburao (Pathapatnam, 2011)
Poor people are not born but they are made by social milieu, inheritance, social structures, local administrative systems, and Governments policy and political will. Since poverty is related to multi-dimensional phenomenon encompassing the inability to satisfy the basic needs, lack of control over resources, lack of education and skills, poor health, lack of food availability, accessibility and food absorption, lack of shelter, poor access to water and sanitation, vulnerability to shock, violence and crime and political freedom and voice. The challenges facing the poorest of the poor and for overcoming poverty are therefore, varied and complex, especially in case of Andhra Pradesh. Limited success of anti-poverty programmes, lack of empowerment, limited livelihood opportunities, limited human capital development, risk faced by the poor and piece-meal approach to poverty reduction by the Government. Since independence, Central and State Governments are putting strenuous efforts to bring under-privileged sections such as SC, ST and BCS etc., in the mainstream of the economy and to improve their socio-economic conditions. Governments have made massive efforts for the socio-economic development of the these sections through organised economic-planning along with planned developmental programmes, and through constitutional safe guards, protective legislations and introduction of developmental agencies (like GCC, ITDA, DRDA, SC & BC Corporation etc), there is a very little impact of development, in spite of spending large amount on these sections. There are gaps in the level of development since beginning-of-selection, planning, implementation, monitoring of stakeholders as well as administrators concerned.
Keywords: Poverty